The Role of Modern Educational Technology in Teaching Reform in Chinese Rural Schools-A Case of Rural School in Zhao Ming, Xiang Yang City - Wenshung, Liu; Anwar, Khoirul (Prosiding University Research Colloquium, 2025)
Focusing on Zhaoming Middle School in Xiangyang City, this study investigates how contemporary educational technology is incorporated into teaching reform in Chinese rural schools. The study intends to evaluate the present level of technology adoption, pinpoint important variables impacting its efficacy, and investigate implementation-related obstacles. By tackling these issues, the study adds to the larger conversation about educational equity and how technology might help close the gap between rural and urban areas. Both qualitative focus group discussions and quantitative surveys were included in the mixed-methods approach. Teachers from Zhaoming Middle School comprised the study’s population; 400 questionnaires were sent out, and 355 valid answers (88.75% response rate) were gathered. Six instructors from different fields also participated in focus groups, offering deep insights into technology difficulties. Perceived usefulness, perceived ease of use, perceived value, and efficacy of digital tools were measured using a 19-item Likert-scale questionnaire, and recurrent themes in teacher experiences were identified by thematic analysis. The results show that teachers have a generally positive attitude toward technology and recognize its potential to improve student engagement and instructional efficiency. Nevertheless, Significant obstacles exist, such as inadequate infrastructure, teacher training, unequal student access, and poor policy implementation. Statistical findings from structural equation modeling, or SEM, support perceived value’s impact in promoting digital literacy and learning behaviors. The study’s conclusions provide theoretical contributions to technology acceptance models in education and useful advice for legislators, educators, and technology developers in forming rural digital education reforms. The study’s implications underscore the necessity of focused infrastructure investment, extensive teacher training programs, and more robust policy enforcement to guarantee sustainable technological integration in rural schools.